Risk factors associated with periodontal disease and its impact on quality of life among pregnant women - Hsiang-Hsi Hong; Yi-Heng Chen; Po-Jen Cheng; Min-Yu Chang; Li-Lan Chuang (Taylor & Francis Group, 2023)
Background Periodontal disease during pregnancy affects maternal oral health and increases the risk of adverse pregnancy outcomes. However, studies on the risk factors for periodontal disease and its impact on oral health-related quality of life in pregnant women in Taiwan are lacking. This present study aimed to identify the risk factors associated with periodontal disease during pregnancy and examine the relationship of periodontal disease with oral health-related quality of life among pregnant women. Methods This study was conducted in a large medical centre in northern Taiwan. Eighty-four participants completed a periodontal examination by dentists as well as structured questionnaires, including the Oral Health Impact Profile-14, demographics, obstetric history, dietary habits, and oral hygiene behaviours. Multivariate logistic regression was used to determine the risk factors associated with periodontal disease and a t-test was used to compare the difference in oral health-related quality of life between pregnant women with and without periodontal disease. Results Fifty participants (59.5%) had periodontal diseases. Risk factors for periodontal disease included eating out for lunch, consuming beverages, brushing less than three times per day, and not receiving regular professional dental cleanings. The oral health-related quality of life was significantly poorer in pregnant women with periodontal disease than in those without. Conclusions The risk factors for periodontal disease, including eating out for lunch, drinking beverages, brushing teeth less, and not regular dental cleaning, provide convincing evidence for pregnant women to maintain good oral hygiene to prevent periodontal disease and improve oral health-related quality of life.